Deposition of nanolayers by means of dense plasma focus - Chernyshova, M.; Ivanova-Stanik, I.; Karpinski, L.; Scholz, M.; Ulejczyk, B.; Demchenko, I. N.; Lee, J. K. (INST PHYSICS ACAD SCI CZECH REPUBLIC, 2006)
In our preliminary experiments, reported in this paper, dense plasma focus (DPF) device is used for deposition of thin (a few nanometers of thickness) chromium layers. Such films have been deposited on silicon wafers by ablation of the chromium target using highly dense and highly temperature argon-oxygen plasma. Two films with different structure were obtained at the same substrate temperature using a fixed shot number (equal to 7). Surface topology and depth profiles of the films were studied by means of scanning electron microscopy (SEM) and secondary ion mass spectrometry (SIMS), respectively.
Keywords: X-RAY-LITHOGRAPHY